Activity of strains of Metarhizium anisopliae (Metsch) Sorokin against white grub (Chiloloba acuta, Scarabaeidae, Coleoptera) under laboratory condition in Nepal - Khanal, Dipak (Journal of Agriculture and Environment, 2018)
Soil insect pests are the major productivity constrains of different crops among which white grubs (Coleoptera: Scarabaeidae), both adult and larval stages, are extremely destructive in nature. Laboratory studies were conducted to evaluate the virulence of an indigenous and a commercial strain of the entomopathogenic fungi, Metarhizium anisopliae (Metsch.) Sorokin, against white grubs species Chiloloba acuta by applying the dipping method at Entomology Division, NARC, Nepal. Third instars larvae of C. acuta were dipped in suspensions of indigenous and commercial strains (Pacer) of M. anisopliae at different concentrations ranging from 3.33×104 to 1.04×108 spores/ml for 3-5 seconds which resulted in 97.8% and 89% mortalities with the highest dose of 1.04×108 spores/ml 40 days after inoculation (DAI), respectively. The LC50 values for indigenous and commercial strain were 3.5×105 and 1.88×106 spores/ml, respectively, with the potency of 1:0.28 at 40 DAI. Bioassays were conducted in completely randomized design. From results it is concluded that the tested strains of entomopathogenic fungi have potential as microbial control agents in managing white grubs in laboratory and it is suggested to be tested under farmers field condition.